Expression of recombinant T1 lipase in E. coli strain W using fifth grade molasses as carbon source - Yusoff, Siti Hajar (2019)
T1 lipase is suitable for various industrial applications due to its thermoalkaliphilic property. However, for industrial purposes normally large scale cultures are used and the current plasmid-based expression system raised concerns for the cost of antibiotics, dissemination of antibiotics and metabolic burden that could lead to reduction of recombinant protein productivity. Furthermore, the overall production cost depends greatly on the source of carbon. Therefore, many attempts have been made to produce recombinant proteins in E. coli from molasses, a cheap carbon source. However, most E. coli cannot utilize sucrose which is the major sugar in molasses. The aim of this study is to solve these problems by expressing the recombinant lipase using genome-based expression in E. coli W. E. coli W was chosen because it is the only safe laboratory strain that can utilize sucrose and shows fast, highly oxidative sucrose metabolism with low acetate production. The objectives of this study are to clone and integrate lipase gene into E. coli W genome, to express the recombinant lipase and to optimize the production of the recombinant product. The T1 lipase gene cassettes with different promoters (tac and trc promoters) were successfully cloned and integrated into E. coli W for plasmid based and genome based expression respectively. The expression of T1 lipase in E. coli W were higher in plasmid-based expression system compared to genome-based expression system but both systems have higher expression under trc promoter (thus, it was chosen for further study). Optimization study recorded the highest expression of T1 lipase at induction temperature of 16°C, 0.8 mM of IPTG concentration and 3% of molasses in M9 medium. A combination of the approaches described above may permit the industrial scale utilization of E. coli for bioconversion of low-cost starting materials (sucrose-molasses) into industrially important enzymes. Furthermore, production of recombinant lipase from the stable expression in the genome can be a model for production of other industrially important recombinant proteins.